Cercopithecoid humeri from Taung support the distinction of major papionin clades in the South African fossil record. Issue 90 (January 2016) - Gilbert, Christopher C.; Takahashi, Maressa Q.; Delson, Eric
Abstract: Associated cercopithecoid postcrania are rare in the Plio-Pleistocene fossil record, particularly in the case of South African karst cave sites. However, as clear postcranial differences between major papionin clades have been documented, it should be possible to assign isolated papionin postcrania to the Cercocebus/Mandrillus and Papio/Lophocebus/Theropithecus groups wherever sufficient anatomy is preserved. Here, we demonstrate that two partial humeri preserved at Taung, UCMP 56693 and UCMP 125898, are most likely attributable to the Cercocebus/Mandrillus and Papio/Lophocebus/Theropithecus clades, respectively. Univariate analyses (ANOVAs and t -tests) and multivariate analyses (discriminant function analyses) of humeral features, combined with a phylogenetic analysis of 24 humeral characters, all support our assessment. Given that the overwhelming number of craniodental specimens at Taung are attributable to two papionin taxa, Procercocebus antiquus (a member of the Cercocebus/Mandrillus clade) and Papio izodi (a purported fossil species of the modern genus Papio ), we assign UCMP 56693 to Pr. antiquus and UCMP 125868 to P. izodi with a high degree of confidence. Implications for cercopithecoid evolution and biogeography are discussed, with a particular emphasis on these two fossil taxa.